Exploratory practice model for and with English language teaching students - Aylin Köyalan1 (Literacy Trek)
This article reports a practitioner research in which third grade students of an English Language Teaching program are taught how to conduct practitioner research to highlight the importance of exploring the classroom in more detail and to improve their own classroom teaching. In the academic year 2023-2024, Fall term, the instructor decided to introduce practitioner research by conducting one herself. The students participated in all phases of the collective meaning-making. The target puzzlement was to deal with the problem of silent students. First, Paphamihiel (2002)’s English Language Anxiety Scale was used to measure the students’ level of anxiety. Secondly, two volunteer students were included as co-researchers and they watched the lesson recordings and identified the silent students. Lastly, those students were interviewed to investigate the reasons why they were silent. Our findings showed that their silence could be attributed to personal issues and not to the course or the course tutor in particular.